Kinetic Estimation of GFR Improves Prediction of Dialysis and Recovery after Kidney Transplantation - Pianta, Timothy J.; Endre, Zoltan H.; Pickering, John W.; Buckley, Nicholas A.; Peake, Philip W. (PLOS ONE, 2015)
Background The early prediction of delayed graft function (DGF) would facilitate patient management after kidney transplantation. Methods In a single-centre retrospective analysis, we investigated kinetic estimated GFR under non-steady-state conditions, KeGFR, in prediction of DGF. KeGFRsCr was calculated at 4h, 8h and 12h in 56 recipients of deceased donor kidneys from initial serum creatinine (sCr) concentrations, estimated creatinine production rate, volume of distribution, and the difference between consecutive sCr values. The utility of KeGFRsCr for DGF prediction was compared with, sCr, plasma cystatin C (pCysC), and KeGFRpCysC similarly derived from pCysC concentrations. Results At 4h, the KeGFRsCr area under the receiver operator characteristic curve (AUC) for DGF prediction was 0.69 (95% CI: 0.56–0.83), while sCr was not useful (AUC 0.56, (CI: 0.41–0.72). Integrated discrimination improvement analysis showed that the KeGFRsCr improved a validated clinical prediction model at 4h, 8h, and 12h, increasing the AUC from 0.68 (0.52–0.83) to 0.88 (0.78–0.99) at 12h (p = 0.01). KeGFRpCysC also improved DGF prediction. In contrast, sCr provided no improvement at any time point. Conclusions Calculation of KeGFR from sCr facilitates early prediction of DGF within 4 hours of renal transplantation.